Pre-service english teachers' challenges in teaching young learners - Naranjo Sánchez, Mayra Jackeline (2024)
This research project aimed to identify the challenges in the teaching experience by pre-service teachers from the Technical University of Cotopaxi in young students, therefore, the study focused on the problem of what are the most common challenges encountered in teaching practice with emphasis on the results/data obtained from students who have already passed their internship process. In addition, a methodology based on the qualitative approach was applied through the descriptive method with the help of a virtual dialogue between the interviewer and interviewee. The sample consisted specifically of eight students from the Technical University of Cotopaxi who completed their pre-professional internships. The technique used was the semi-structured interview and the analysis of the information collected and stored in multimedia devices. The result of this study indicated that pre-service teachers have the necessary resources to create a solid teaching practice. However, pre-service English teachers face numerous challenges, such as the correct application of their knowledge in the classroom and the impossibility of managing a group of more than thirty students, confidence, motivation, time, and resource pressures. Although, based on their learning experience, they have many strategies to resolve impediments.